Dialektika Islam Nusantara Di Ruang Digital : Pergulatan Narasi dan Otoritas Dalam Debat Gus Ajir Vs Herri Pras - Moh. Jazuli; Yusril Amin Faqih; Ilham Firmansyah (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The debate between KH. Ajir Ubaidillah (Gus Ajir) and Herri Pras in January 2026 represents a significant phenomenon in the study of Islam Nusantara in the digital age. This article examines the debate as a site of contestation between two religious approaches: the sanad-based scholarly tradition (Aswaja) and literal-scriptural criticism of traditional practices. Utilizing a digital discourse analysis approach, this study demonstrates that the debate on tabarruk, karamah, and khurafat is not merely a theological argument but rather a reflection of the fragmentation of religious authority in the digital public sphere. This article argues that the debate embodies a clash between the "aesthetics of authority" grounded in scholarly chains of transmission and the "aesthetics of virality," which relies on digital popularity and provocative content. This study reveals how social media platforms serve as contested arenas where competing epistemological claims are negotiated. The findings suggest that while digital platforms intensify ideological polarization, they also offer potential for constructive dialogue particularly when neutral third-party mediators such as the Gawagis Muhammadiyah Forum facilitate the discussion. This research contributes to broader scholarly conversations on religious authority, digital da'wah, and the evolving landscape of Islamic discourse in contemporary Indonesia.